Taxonomía de las especies neotropicales de Marattia (Marattiaceae) - Lavalle, María del Carmen (2003)
This paper deals with a revised taxonomy of seven neotropical species of the genus Marattia (M. alata, M. cicutifolia, M. excavata, M. interposita, M. laevis, M. laxa y M. weinmanniifolia), based on morphological characters of the sporophyte, both vegetative and reproductive. A new and detailed description of the species is provided, along with synonymy, comments on habitat, geographical distribution and a complete list of the studied specimens. A key to identify the species is also given.